Simplify:

(i) (-4)^{3}

(ii) (-3) × (-2)^{3}

(iii) (-3)^{2} × (-5)^{2}

(iv) (-2)^{3} × (-10)^{3}

(i) We simplify the given expression (-4)^{3} as:

(-4)^{3} = (-4) × (-4) × (-4)

= - 64

(ii) We simplify the given expression (-3) × (-2)^{3} as:

(-3) × (-2)^{3} = (-3) × (-2) × (-2) × (-2)

= (-3) × (-8)

= 24

(iii) We simplify the given expression (-3)^{2} × (-5)^{2} as:

(-3)^{2} × (-5)^{2} = (-3) × (-3) × (-5) × (-5)

= 9 × 25

= 225

(iv) We simplify the given expression (-2)^{3} × (-10)^{3} as:

(-2)^{3} × (-10)^{3} = (-2) × (-2) × (-2) × (-10) × (-10) × (-10)

= (-8) × (-1000)

= 8000

12